Roles of non-coding RNAs in the hormonal and nutritional regulation in nodulation and nitrogen fixation - Fan, Kejing; Sze, Ching-Ching; Li, Man-Wah; Lam, Hon-Ming (Frontiers in Plant Science, 2022)
Symbiotic nitrogen fixation is an important component in the nitrogen cycle and is a potential solution for sustainable agriculture. It is the result of the interactions between the plant host, mostly restricted to legume species, and the rhizobial symbiont. From the first encounter between the host and the symbiont to eventual successful nitrogen fixation, there are delicate processes involved, such as nodule organogenesis, rhizobial infection thread progression, differentiation of the bacteroid, deregulation of the host defense systems, and reallocation of resources. All these processes are tightly regulated at different levels. Recent evidence revealed that non-coding RNAs (ncRNAs), including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), participate in these processes by controlling the transcription and translation of effector genes. In general, ncRNAs are functional transcripts without translation potential and are important gene regulators. MiRNAs, negative gene regulators, bind to the target mRNAs and repress protein production by causing the cleavage of mRNA and translational silencing. LncRNAs affect the formation of chromosomal loops, DNA methylation, histone modification, and alternative splicing to modulate gene expression. Both lncRNAs and circRNAs could serve as target mimics of miRNA to inhibit miRNA functions. In this review, we summarized and discussed the current understanding of the roles of ncRNAs in legume nodulation and nitrogen fixation in the root nodule, mainly focusing on their regulation of hormone signal transduction, the autoregulation of nodulation (AON) pathway and nutrient homeostasis in nodules. Unraveling the mediation of legume nodulation by ncRNAs will give us new insights into designing higher-performance leguminous crops for sustainable agriculture.